Human capital formation, asymmetric information, and the dynamics of international migration - Oded Stark; Nancy H. Chau (Institute for Advanced Studies (IHS), 1998)
We consider the case in which the opening up of an economy to migration results in departure of skilled workers. We point out that while the possibility of migration changes the set of employment opportunities, it also affects the structure of incentives: Higher returns to skills in the foreign country influence decisions about skill acquisition at home. We combine the changing opportunities - changing incentive structure idea with an assumption concerning the information environment: Employers in the foreign country are neither perfectly informed nor equally informed over time about the skill levels of individual migrant workers as employers' experience of employing migrant workers accumulates. Our model gives rise to several interesting results. First, while migration is pursued by the relatively high-skilled, subsequent return migrants are drawn from both tails of the migrant skill distribution. Second, the fraction of the home-country workforce acquiring education in the presence of migration opportunities is higher than the fraction of the home-country workforce acquiring education in the absence of migration opportunities. Third, the intertemporal increase in the probability of discovery of individual skill levels prompts a sequence of migratory moves characterized by a rising average skill level, until the probability of discovery arising from accumulation of migrant employment experience reaches its steady state equilibrium. Finally, under well-specified conditions, per capita output in a country vulnerable to migration of skilled members of its workforce is higher than per capita output in a country that is immune to migration.
Keywords: J24; F22; 330; human capital; asymmetric information; international; migration; Humankapital; Internationale Arbeitsmobilität; Asymmetrische Information; Theorie